2021
DOI: 10.1080/10408398.2021.1974336
|View full text |Cite
|
Sign up to set email alerts
|

Meat and mental health: A meta-analysis of meat consumption, depression, and anxiety

Abstract: in this meta-analysis, we examined the quantitative relation between meat consumption or avoidance, depression, and anxiety. in June 2020, we searched five online databases for primary studies examining differences in depression and anxiety between meat abstainers and meat consumers that offered a clear (dichotomous) distinction between these groups. Twenty studies met the selection criteria representing 171,802 participants with 157,778 meat consumers and 13,259 meat abstainers. we calculated the magnitude of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 68 publications
2
10
0
Order By: Relevance
“…Regarding each food group, previous studies revealed that the association between meat and depression might be represented as a "U" shape. Although one meta-analysis showed a protective effect of moderate meat intake associated with lower depression and anxiety compared with meat abstention [34], excessive intake of meat, especially red meat, was associated with a higher risk of depression [35]. Meanwhile, a previous study revealed that not consuming three servings of nuts a week and not eating two servings of vegetables a day are predictors of depression, which supports our data [35].…”
Section: Ppd-related Dietary Patternsupporting
confidence: 84%
“…Regarding each food group, previous studies revealed that the association between meat and depression might be represented as a "U" shape. Although one meta-analysis showed a protective effect of moderate meat intake associated with lower depression and anxiety compared with meat abstention [34], excessive intake of meat, especially red meat, was associated with a higher risk of depression [35]. Meanwhile, a previous study revealed that not consuming three servings of nuts a week and not eating two servings of vegetables a day are predictors of depression, which supports our data [35].…”
Section: Ppd-related Dietary Patternsupporting
confidence: 84%
“…Other studies only concluded gender differences; male vegetarians demonstrated higher depression than male omnivores, but females did not [ 38 ]. Interestingly, a recent meta-analysis of over 170,000 participants concluded that people who eat meat, predominantly omnivores, had lower depression than plant-based diet samples [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research by Abrhaley and Leta [ 51 ] has shown that camel meat is a good source of nutrients, both in terms of composition (including low fat and cholesterol content) and declared health effects, which is especially evident in Somalia and India. In addition, the complete elimination of meat from the diet may worsen mental health, in particular causing depression and anxiety [ 52 ]. A future solution of cultured meat [ 53 ], also known as slaughter-free, lab-grown, or synthetic meat seems inevitable.…”
Section: Discussionmentioning
confidence: 99%